Machine vision for the measurement of machining parameters: A review - Abdul Wahab, Hashmi; Mali, Harlal Singh; Meena, Anoj; Khilji, Irshad Ahamad; Mohammad Farukh, Hashmi; Siti Nadiah, Mohd Saffe (2022)
Machining parameters have significant value in manufacturing and machining industries as they result in quality and dimensional accuracy of the product. The machining parameters are measured using various machine vision systems. In this review, machine vision and its various procedures have been discussed that are used to measure machining parameters, i.e., tool condition monitoring (TCM) tool wear and surface characteristics like surface roughness, surface defects, etc. Nowadays, Tool condition monitor is a significant machining parameter is developed in manufacturing and machining industries. The development of various techniques of machine vision explore in tool condition monitoring is of significant interest because of the improvement of non-tactile applications and computing hardware. The review also discusses the enhancement of machine vision systems in tool condition monitoring.